Toxic effects of virtako on the brown planthopper, Nilaparvata lugens (Hemiptera: Delphacidae) - Chen, Yong; Qing, Xiaowa; Liu, Jie; Zhang, Jie; Zhang, Runjie (Revista Colombiana de Entomología, 2013)
Laboratory assays (Institute of Entomology, Sun Yat-Sen University, Guangzhou, China) were conducted to assess the potential of virtako, a mixture insecticide, which contains 20% chlorantraniliprole and 20% thiamethoxam, against the brown planthopper, Nilaparvata lugens (Hemiptera: Delphacidae). The toxic effects of virtako against the nymphal instars of N. lugens indicated that all instars were sensitive to the five concentrations (16, 8, 4, 2, 1 mg/L). The first-second instars were the most susceptible, and the median lethal concentrations [LC50] were 4.76, 1.96 and 0.85 mg/L at 24, 48 and 72 h after treatment, respectively. Fifth-instars were the least susceptible with the LC50 values of 23.76, 7.25 and 3.95 mg/L at 24, 48 and 72 h after treatment, respectively, and were significantly greater than those of the first - second instars. The LC50s of the third - fourth instars were 11.59, 5.72 and 2.17 mg/L at 24, 48 and 72 h after treatment, respectively. These results indicate that virtako might be an effective alternative for the control of BPH N. lugens, by delaying the resistance levels of thiamethoxam.